MO806: Change in Pth Measuring Method Affects the Cost of Pth-Lowering Treatment. (3rd May 2022) - Kuroki, Aki; Shimura, Satoru; Kikuchi, Rie; Yanagida, Toshihiro; Tsuboi, Takahiro; Inagaki, Kazuyuki; Ohashi, Yasushi
Abstract: BACKGROUND AND AIMS: To control mineral and bone disorders in haemodialysis (HD) patients, doses of vitamin D analogues and calcimimetics are adjusted based on serum parathyroid hormone (PTH) levels. Accordingly, method-related differences in PTH results may influence the prescribed dose of those drugs and PTH-lowering treatment costs. The aim of this study was to clarify the influence of inter-method variability in PTH measurement on PTH-lowering treatment costs. METHOD: We used data from 30 maintenance HD patients in our facility. The Intact-PTH measuring assay was changed from the Elecsys PTH to the Alinity Intact PTH Reagent Kit (Alinity PTH) in March 2021, following a 2-month transitional period when PTH levels were measured using both assays. We examined method-related differences in PTH levels, using the results obtained in the transitional period. Using prescription records from October to December 2020, when the Elecsys PTH assay was used, and those from March to May 2021, when assay system was fully changed to the Alinity PTH, we examined the influence of the PTH measuring method on medication cost by evaluating the monthly cost of vitamin D analogues and calcimimetics in our facility. We evaluated the mean levels of serum calcium, phosphorus and PTH in 30 patients in the corresponding period. RESULTS: Inter-method variability in PTH results was evaluated using 60 specimens from 30 patients. PTH results of 60 specimens ranged from 11 to 802 pg/mL and 8.8 to 1198 pg/mL in the Elecsys PTH and in the Alinity PTH, respectively. Compared with PTH levels obtained with the Elecsys PTH, those measured with the Alinity PTH were significantly higher ( P < .001). On average, results obtained with the Alinity PTH were 1.58-fold higher than those provided by the Elecsys PTH. When the Elecsys PTH assay was used, the average monthly cost of vitamin D analogues and calcimimetics was €44 and €1668, respectively. After the assay was changed to the Alinity PTH, the average monthly costs were €40 for vitamin D analogues and €2471 for calcimimetics (€1 = ¥130). There were no notable changes in the mean serum levels of calcium, phosphorus and PTH throughout the study period. CONCLUSION: Inter-method variability in PTH results would have an influence on the cost-effective assessment of PTH lowering therapy. Standardization of PTH measurement is required.